A case of rapidly progressing sarcomatous intrahepatic cholangiocarcinoma with suddenly appearing lymph node metastasis - Eisho Kanemitsu; Rei Takahashi; Setsuko Nakanishi; Satoru Sueyoshi; Atsushi Kobayashi; Takao Nishimura; Hiromitsu Nagata (Surgical Case Reports)
Abstract Background The sarcomatous variant of carcinoma is relatively rare in intrahepatic cholangiocarcinoma (ICC). Sarcomatous ICC (SICC) is associated with a poorer prognosis compared with ICC. SICC is rarely diagnosed before surgery due to non-descriptive findings; it progresses rapidly, resulting in miserable prognosis. Here, we report a case of rapidly progressing SICC that showed a clinically significant tumor growth rate. Case presentation A 77-year-old woman who had undergone ileocecal resection for cecal cancer 5 years previously was found to have elevated levels of the tumor marker carbohydrate antigen 19-9. Although an abdominal computed tomography (CT) scan did not detect any liver mass lesions until 3 months before this serum examination, the subsequent CT scan revealed a hypodensity 20 mm mass lesion in the right anterior section. Contrast-enhanced CT and magnetic resonance imaging revealed peripheral enhancement in the arterial-to-equilibrium phase. Fluorodeoxyglucose positron emission tomography revealed uptake in the lesion. None of the imaging modalities showed lymph node swelling or distant metastases. She underwent hepatectomy under the diagnosis of ICC or an atypical metastasis from previous cecal cancer. Although preoperative images showed no suspicious lymph node metastasis 3 weeks prior, the hilar lymph node swelled 3 cm and contained adenocarcinoma. Consequently, the patient underwent right anterior sectionectomy and lymph node dissection of the hepatoduodenal ligament. Histopathological examination revealed that the liver tumor was a poorly differentiated adenocarcinoma with sarcomatous pattern. While the patient received adjuvant gemcitabine and S-1 therapy, lymph node metastasis appeared in the mediastinum 13 months after the surgery. She received gemcitabine + cisplatin + S-1 therapy but died 20 months after surgery. Conclusion SICC and lymph node metastasis clinically appeared within 3 months and 3 weeks, respectively. Suspected ICC that rapidly progresses should be considered SICC and treated with early resection. SICC is often missed in clinical diagnosis and has a poor prognosis, even after curative resection. While an alternative strategy involving preoperative biopsy and neoadjuvant therapy may be beneficial, it should be approached with discretion due to the potential risks of tumor progression and peritoneal dissemination.